Proteasomal activation ameliorates neuronal phenotypes linked to FBXO11-deficiency - Anne Gregor; Laila Distel; Arif B. Ekici; Philipp Kirchner; Steffen Uebe; Mandy Krumbiegel; Soeren Turan; Beate Winner; Christiane Zweier (HGG Advances)
Summary: Haploinsufficiency of FBXO11, encoding a ubiquitin ligase complex subunit, is associated with a variable neurodevelopmental disorder. So far, the underlying nervous system-related pathomechanisms are poorly understood, and specific therapies are lacking. Using a combined approach, we established an FBXO11-deficient human stem cell-based neuronal model using CRISPR-Cas9 and a Drosophila model using tissue-specific knockdown techniques. We performed transcriptomic analyses on iPSC-derived neurons and molecular phenotyping in both models. RNA sequencing revealed disrupted transcriptional networks related to processes important for neuronal development, such as differentiation, migration, and cell signaling. Consistently, we found that loss of FBXO11 leads to neuronal phenotypes such as impaired neuronal migration and abnormal proliferation/differentiation balance in human cultured neurons and impaired dendritic development and behavior in Drosophila. Interestingly, application of three different proteasome-activating substances could alleviate FBXO11-deficiency-associated phenotypes in both human neurons and flies. One of these substances is the long-approved drug Verapamil, opening the possibility of drug repurposing in the future. Our study shows the importance of FBXO11 for neurodevelopment and highlights the reversibility of related phenotypes, opening an avenue for potential development of therapeutic approaches through drug repurposing.